EXAMINATION IN THEORY OF ACCOUNTS. - Zlatkovich, Charles T. (The Accounting Review, 1964)
Abstract The article presents questions which appeared in the May, 1964, Uniform Certified Public Accountants (CPA) Examination. It was held on Friday, May 15, from 1:30 p.m. to 5:00 p.m. There were seven questions in all. The article also presents solution to the problems given in the question paper. Answers which follow are intended to typify those submitted by well-prepared candidates writing within the time limits prescribed. They do not necessarily include all elements for which credit might be given by the Advisory Grading Service of the American Institute of CPA or by the various state accountancy boards charged with the responsibility of issuing CPA certificates. One of the questions was related to expenditure. The candidates were asked to distinguish between capital expenditures and revenue expenditures, and their treatments in the accounts. They were also asked to distinguish between these two categories of expenditures and between their treatments in the accounts. The candidates were to discuss the impact on both present and future balance sheets and income statements.